(Un)gewolltes Aufbegehren: (Dis)adattamento linguistico nelle traduzioni tedesche di Giuseppe Ungaretti (TEST Ticontre. Theory Text Translation, 2026)
The act of translating the oeuvre of Giuseppe Ungaretti into German demands a dual undertaking on the part of translators: the preservation of the poet’s surreal imagery whilst maintaining the semantic ambiguity that characterises his oeuvre to a remarkably high degree. Translation into a language such as German also necessitates compliance with different rules, particularly in terms of syntax, morphology and word formation. Ungaretti’s poetic texts, especially in the first decades of their reception in the German-speaking world (namely from the 1930s to the early 1960s), were translated individually in many literary magazines and anthologies and ‘reinterpreted’ by numerous intellectuals, Italian literature scholars and distinguished readers. Since 1960, the already considerable number of Ungaretti’s translators has been further augmented by the incorporation of eminent figures in German-language literature, including Ingeborg Bachmann, Paul Celan, Hans Magnus Enzensberger and Hilde Domin. This continuous negotiation (which had singular outcomes both before and after the ‘watershed’ 1960) led to the establishment of reference points that could be literary-cultural or purely linguistic. It is at these points that each translator of Ungaretti elects to ‘adapt’ or ‘de-adapt’ the German text from the original. The present contribution aims to identify the linguistic aspects (in terms of semantics, metre, syntax, morphology, productivity and lexicon) in which both adaptations and de-adaptations occur.